Nonlinear ship motion with forward speed in waves based on 3D time domain hybrid Green function method. (1st February 2021) - Tang, K.; Wang, J.X.; Chen, X.; Jiang, D.P.; Li, Y.L.
Abstract: In this research, based on three-dimensional (3D) time domain hybrid Green function method, the time-domain nonlinear initial boundary value problem of a ship motion in waves with forward speed is solved. The 3D Rankine source and 3D time domain free surface Green function are adopted to solve flow fields of the inner and the outer domains respectively. Meantime, the instantaneous wet surface during ship motion is divided into boundary elements in every time step, to calculate nonlinear incident wave and static restoring forces. Combining with the linear solution of radiation and diffraction problems, the nonlinear time domain numerical method based on 3D hybrid Green function method for ship motion in waves with forward speed is established. Numerical simulation and analysis are carried out for Wigley and S175 ships with different forward speeds and wave angles respectively by developed numerical solver. The comparison with the experimental results show that the proposed nonlinear numerical method has an obvious improvement in predicting accuracy under complicated conditions such as with higher forward speed and large flare, which proves it has good prospect in engineering applications.